Nübüvveti ispat açısından hissi mucizeler - Bulut, Halil İbrahim (My University, 2001)
İslam inanç esaslarını uluhiyet, nübüvvet ve ahiret üçlüsü oluşturmaktadır. Peygamberliğin imkan ve ispatını, mahiyet ve özelliklerini konu edinen nübüvvet bahisleri, diğer iki konuya oranla daha fazla tartışılmıştır. Semavi dinler, Tanrı ile insanlar arasında bağlantı kuran bir peygamberler zümresinin bulunduğu hususunda ittifak etmekle birlikte, peygamberlik iddiasında bulunan her hangi bir kimsenin söz konusu zümreye mensubiyeti hususunda ihtilaf edilmiştir. Bu bakımdan Allah elçisi olduğunu iddia eden bir kimsenin gerçek peygamber olduğunun nasıl bilineceği önemli bir problemdir. Bu çalışmada, aklî ve hissî olmak üzere iki grupta toplanan mucizelerden sadece hissî mûcizelerle peygamberliğin ispat edilmesi konusuna ağırlık verilmiş, Kur'an, hadis ve kelâm literatürünün bu konudaki yaklaşımı ortaya konulmaya çalışılmıştır. Araştırma, bir giriş ve iki bölümden meydana gelmektedir. Girişte mûcize kavramı üzerinde durulmuş; mûcizenin ne olduğu, ne tür özellikler taşıdığı ve hangi olayların mûcize kabul edileceği hususu izah edilmiştir. Kelâm literatürüne ait bir ıstılah olması bakımından mûcize teriminin hangi dönemden itibaren kavramlaştığı tespit edilmeye çalışılmış, kelâm kaynaklarına göre mûcizede bulunması gereken temel özellikler ve bunlarla ilgili argümanlar ortaya konulmuştur. Kur'an'da zikredilen mûcizeler konu, hedef, içerik ve benzeri açılardan tasnif edilmiş ve bunların temel özellikleri açıklanmıştır. Girişin ikinci kısmında hârikulâde olayların imkanı meselesi ele alınmış ve mucizeyle farklılıkları açıklanmıştır. Birinci bölümde Kur'an'da mûcize kavramını karşılayan terimler üzerinde durulmuş ve bilahare mûcize-nübüvvet ilişkisine geçilmiştir. Burada peygamberliğin ispatında mûcizenin bir gereklilik olup olmadığı hususu Kur'an ve kelâm literatürüne göre ayrı ayrı ele alınmış ve aynı tarzda mûcizenin nübüvvete delâlet edişi konusuna yer verilmiş; bu delâletin şekil ve mahiyeti ile ne tür bilgi ifade ettiği konusu işlenmiştir. Ayrıca müstakil başlıklar altında mûcizelerin imanın oluşumundaki rolü, peygamberlerin başarılarındaki katkıları ve zaman- mekanla irtibatları izah edilmeye çalışılmıştır. İkinci bölümde önce inkarcılar tarafından peygamberlere yöneltilen itirazlar anlatılmış, sonra geçmiş peygamberler ile son Peygamber'den istenilen mûcizeler ve bu isteklere verilen cevaplar ayrı ayrı değerlendirilmiş ve bilahare genel olarak mûcizeleri inkar etmenin sebepleri üzerinde durulmuştur. İkinci kısımda Hz. Peygamber'e atfedilen hissî mûcizelerin Kur'an çerçevesinde neler olduğu tespit edilmiş ve bunlar ayrı başlıklar halinde açıklanmıştır. İlk olarak İnşikâku'l-kamerin hissî bir mûcize oluşu meselesi, önce Kur'an çerçevesinde sonra da hadis ve kelâm literatürüne göre açıklanmıştır. İkinci olarak Bedir Savaşında meleklerin yardıma gelişlerinin hissî bir olay olup olmadığı değerlendirilmiştir. Bu kısımda son olarak Hz. Peygamber'in savaş sırasında kafirlere bir avuç toprak serpmesi ve bunun hissî bir mûcize olarak sunulmasıyla ilgili rivâyetler değerlendirilmiştir. İkinci bölümün sonunda Kur'an'ın hissî mûcizeler konusundaki tavrı ele alınmış, önce Hz. Peygamber'e hissî mûcize verilip verilmediği ve bunun sebepleri üzerinde durulmuştur. Bilahare hadis literatüründe Hz. Peygamber'e atfedilen hissî mûcizelerin Kur'an ekseninde genel bir değerlendirilmesi yapılmıştır. İlgili rivâyetleri kabul ve reddedenlerin argümanları verildikten sonra bu tür hadiselerin imkanını kabul etmekle birlikte bunların nübüvvete delil olamayacağını savunanların görüşlerine yer verilmiştir.

A comparision of Turkish High School Students moral judgement abilities in Germany and Turkey The present comparative study examines factors affecting Turkish students moral judgment abilities and how these students perceive the moral atmosphere in their schools and what topics they want to discuss with their teachers. The study was carried out with subjects from different High Schools in Germany and Turkey. The data were collected by applying the Moral Judgment Test by G. Lind (MUT, 1977) and the Questionnaire of Moral Atmosphere (MAF, Lind 1986), and another questionnaire on sociodemographic characteristics and adherence to religious principles designed by the author of the present study. The validity of the Turkish Version of the Moral Judgment Test had been confirmed in previous research. The total number of subject was N=401 students (222 girls, 179 boys) studying in Hamburg, Bursa and Istanbul between the ages of 15-19. Statistical analyses were done using t-Test and binary logistic regression analysis. The factors affecting moral judgment include: sex, age, culture, the type of school, religious denomination, the frequency of discussion of religious topics at home, the desire to have friends of different religious denomination, the pressure by the students' parents to make their children obey islamic rules and the permission to have friends of a different religious denomination. Among these factors the pressure by the student's parents to make their children obey islamic rules was found to have negative effect on moral judgment (OR= 2.52; CI % 95= 1.19 - 5.36; p<0.05). Subjects living in Germany experienced a heavier pressure by their parents to follow islamic rules (OR= 10.67; CI % 95= 1.05 - 91.18; p<0.05), however their mean score on the Moral Judgment Test was significantly higher than in the subjects from Turkey. Key Words: Moral judgement ability, the development of moral judgement ability, moral development and moral education, religious pressure and the development of moral judgement, culture and moral development, Just Community School, the Moral Judgment Test (MUT) and the Questionnaire of Moral Atmosphere (MAF) by G. Lind, cognitive-developmental theory of Lawrence Kohlberg, moral atmosphere of the school, Turkish high school students in Germany, democracy and moral, Lawrence Kohlberg, Georg Lind. The Proof of the Prophethood from the Perspective of Sensible Miracles (Hissî Mûcize) (Abstract) The fundemantal principles of Islam consist of three basic concepts: Divine Unity, the Prophethood, Belief in the Hereafter. However, the possibility and proof of the prophethood had been discussed more than the other two. Although Monotheist religions agreed upon the idea that there is a group of prophets who are the mediator between God and people, it is difficult to confirm or know this or that person is a prophet or not. Therefore, the question of 'how we know a person who claimed his prophecy' is very important problem. The miracles are divided into two groups; a) rational or mental b) sensible. This study has put great emphasis on the sensible miracles on the proof of the prophethood. In addition, it demonstrates the general approach of the Qur'an, Hadith and Islamic Theology towards the miracles. This work contains one introduction, and two main parts. In the introduction, the concept of miracle has been discussed; what is the miracle, what kind of features it has, and what kind of events are considered as miracles have been explained. Because it (miracle) belongs to the terminology of Islamic Theology, it has been tried to determine when it began to be used as a technical term or concept. It has also been studied the main features which are supposed to be existed in the miracles and consequently the discussion centred on the miracles. The miracles exist in the Qur'an are categorised according to their subjects, contents, aims, and then their general features are explained. In the second section of the introduction, the difference between extra-ordinary events and miracle has been shown. In the first part, the substitute terms used in the Qur'an other then miracle are dealt with. After that, the relationship between the miracle and the prophethood has been concentrated on. Here, it has been argued that whether the miracles are necessity or not in the proof of the prophethood from the Qur'an and Islamic Theology's perspective separately. Similarly, the issues such as how the miracles prove the prophethood, the form and content of this proof have been dealt with. Apart from afore-mentioned subjects, this study also discusses under individual titles and subtitles the function of the miracle in the formation of the belief, the contribution of the miracle in the success of the prophet, and the relation between the time and place where miracle occurred. Part Two provides detailed information about the objection of the unbelievers to the prophets. Then the request of miracle from the earlier prophets and the last prophet together with their respond to the unbeliever have been evaluated critically. Finally, the main reasons for denying the miracles have been investigated. In the second section, the sensible miracles attributed to the prophets have been determined and then classified under different titles. First of all, the splitting of the moon as a sensible miracle is discussed from both Qur'anic and tradion's perspective. Secondly, it has been dealt with the question of whether the angel's arrival in Bedir is sensible or not. The last topic in this section is devoted to the prophet's throwing sand on the Meccan pagans n the Battle of Bedir; Whether it is sensible miracles or not. In the final section of Part Two, the attitudes of the Qur'an towards the sensible miracles are discussed. The question and reasons for whether the prophet is given the sensible miracles have been argued. The sensible miracles which are found in the prophetic traditions are re-evaluated from Qur'anic perspective. Having given the arguments of the people (scholars) who accept and reject these reports. the information provided about the people who accept the miracles without confirming their use in the proof of the prophethood. At the end of this study, a general evaluation is provided.
Keywords: Din; İslam Dini; İSLAM DİNİ - KELAM; KELAM; Tefsir ve tefsir ilmi